2007
DOI: 10.1891/154041507780978914
|View full text |Cite
|
Sign up to set email alerts
|

Health Perceptions of Low-Income, Immigrant Spanish-Speaking Latinas in the United States

Abstract: The health outcomes and health practices of immigrant Latinas tend to decrease with acculturation to U.S. culture. The purpose of this pilot study was to investigate health perceptions of first-and secondgeneration, low-income, Spanish-speaking women from Mexico and Central America to learn their views of health and also to identify any differences between subcultures. This investigation was the first phase of a larger study to understand the relationship of physical activity to health, as Latinas define it. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Participation in PA is influenced by accessibility to resources that support PA. People desire to travel to parks, public sports centres, or local private health clubs to pursue PA but lack access to reliable transportation such as private cars, [54,56,57,60,69]. In addition, the availability of peers in close proximity and the location influences walking and other forms of PA for transport [63].…”
Section: Urban Environment: Macrosystem To Mesosystemmentioning
confidence: 99%
“…Participation in PA is influenced by accessibility to resources that support PA. People desire to travel to parks, public sports centres, or local private health clubs to pursue PA but lack access to reliable transportation such as private cars, [54,56,57,60,69]. In addition, the availability of peers in close proximity and the location influences walking and other forms of PA for transport [63].…”
Section: Urban Environment: Macrosystem To Mesosystemmentioning
confidence: 99%
“…Cultural preferences may be a significant factor in fruit and vegetable consumption. In a qualitative study that addressed the health perceptions of first-and second-generation Latina women immigrants, healthy nutritional practices tended to decrease with acculturation to United States culture [28]. One participant remarked, "Nutrition [is different] because here there is not enough; there are vegetables, but we do not like them or we do not know how to prepare them" [28].…”
Section: Accessibility Cost Cultural and Societal Factors Related Tmentioning
confidence: 99%
“…In a qualitative study that addressed the health perceptions of first-and second-generation Latina women immigrants, healthy nutritional practices tended to decrease with acculturation to United States culture [28]. One participant remarked, "Nutrition [is different] because here there is not enough; there are vegetables, but we do not like them or we do not know how to prepare them" [28]. Similarly, in their study of Latina immigrants, Fuentes-Afflick and Hessol [29] found that as duration of US residence increased, the prevalence of obesity increased as well.…”
Section: Accessibility Cost Cultural and Societal Factors Related Tmentioning
confidence: 99%
“…To ensure the educational materials will be successfully employed and to increase the treatment compliance for the hypertensive Latino/Latina MSFWs, HCPs need to be knowledgeable about the patients' barriers to better adherence as well as their unique Additional opportunities for improving BP control exist in the social relationships shared among the Latino MSFW. Personalismo, respecting and honoring dignity, is an important first step when communicating with the Latino population (Hartweg & Isabelli-García, 2007). When developing individuals' medication regimen, HCPs can seek to engage family members as a mechanism to augment adherence to HTN treatment.…”
Section: Education For Hcpsmentioning
confidence: 99%